Complete genome sequence of currant latent virus (genus Cheravirus, family Secoviridae) - Petrzik, Karel; Koloniuk, Igor; Přibylová, Jaroslava; Špak, Josef (Archives of virology, 2016)
The complete nucleotide sequences of RNA1 and RNA2 of the Holandský červený strain of currant latent virus (CuLV) were determined using next-generation sequencing. The RNA1 is predicted to encode a polyprotein 2124 amino acid long with RdRp motifs. The RNA2 is predicted to encode a polyprotein 957 amino acid long with homology to the capsid protein of apple latent spherical virus and cherry rasp leaf virus. Phylogenetic analysis confirms that CuLV is a new distinct member of the genus Cheravirus.
Keywords: RNA virová; Phylogeny; Plant Viruses; rostlinné viry; Sequence Homology; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; genom virový; RNA-viry; Cluster Analysis; sekvenční analýza DNA; Genome, Viral; RNA Viruses; fylogeneze; shluková analýza; vysoce účinné nukleotidové sekvenování; RNA, Viral; High-Throughput Nucleotide Sequencing; Ribes; sekvenční homologie